1247. Dalbavancin in Osteomyelitis and Joint Infections: An Analysis From an Observational, Multicenter, Retrospective Cohort Study of the Real-World Use in Adult Patients. (31st December 2020) - Diaz, Julia Garcia; McGregor, Jennifer; Ramani, Anathakrishnan; Lock, John; Golan, Yoav; Gonzalez, Pedro
Abstract: Background: Dalbavancin (DAL) is approved in the United States (US) and Europe for acute bacterial skin and skin structure infections and exhibits broad spectrum activity against clinically important Gram-positive pathogens including methicillin-sensitive and methicillin-resistant Staphylococcus aureus, and Streptococcus spp. We describe the use of DAL in patients with osteomyelitis or joint infection from a phase 4 observational, multicenter, retrospective cohort study of the real-world use of DAL in adult patients across the US: Dalvance Utilization Registry Investigating Value and Efficacy (DRIVE). Methods: Data were collected between 03/25/2017 and 11/27/2018 and included demographics, disease and pathogen characteristics, antibiotic use, clinical outcome, and safety. Patients with a determinate clinical outcome (success/failure) were included in the evaluable population. Results: Data for 96 patients with osteomyelitis and 33 patients with joint infection (safety population) were entered into this subanalysis. Patient demographics and medical history were broadly similar for patients with osteomyelitis or joint infection. The majority (80.4–100%) of patients received DAL as concurrent therapy and clinical success, defined qualitatively, was achieved in 64.7-87.5% of patients (Fig. 1 ). Most patients received 1 or 2 IV DAL doses (osteomyelitis, 33.3% and 34.6%, respectively; joint infection, 37.5% and 31.3%, respectively); 11.5% and 6.3% of patients with osteomyelitis or joint infection, respectively received >4 doses (Fig. 2 ). Staphylococcus spp. was the most frequently isolated organism at baseline (Fig. 3 ); 61.1% and 35.7% of osteomyelitis and joint infection isolates tested, respectively were resistant to oxacillin. At 60 days post-DAL treatment, numbers of Staphylococcus spp. isolated from both groups decreased (Fig. 3), confirming microbiological cure. The rate of serious adverse events was low (16 events in 7 [7.3%] patients with osteomyelitis, 2 events in 2 [6.1%] patients with joint infection) and consistent with the safety profile of DAL. Fig. 1 Fig. 2 Fig. 3 Conclusion: In this real-world study in patients with Staphylococcal osteomyelitis and joint infection, DAL resulted in high rates of clinical and microbiological success. Disclosures: Jennifer McGregor, RPh, AbbVie (Employee) Anathakrishnan Ramani, MD, FACP, AAHIVS, CIC, Allergan (prior to its acquisition by AbbVie) (Speaker's Bureau) John Lock, PharmD, BCPS, AQ-ID, AbbVie (Employee) Pedro Gonzalez, MD, MT, AbbVie (Employee)